Expanding molecular and clinical spectrum of CPT1C‐associated hereditary spastic paraplegia (SPG73)—a case series - Alexandra K. Brooks; Vicente Quiroz; Luca Schierbaum; Amy Tam; Julian E. Alecu; Darius Ebrahimi‐Fakhari (Annals of Clinical and Translational Neurology)
Abstract Autosomal‐dominant variants in the CPT1C gene have been associated with hereditary spastic paraplegia type 73 (SPG73), which typically presents with slowly progressive lower limb weakness and spasticity and is therefore considered a pure form of hereditary spastic paraplegia. However, we report two unrelated males with novel CPT1C variants (NM_001199753.2: patient 1: c.2057_2061del (p.Ile686SerfsTer8) and patient 2: c.2020‐1G>C (p.?)) who presented with lower limb spasticity at 4 and 3 years old, respectively. Both patients also experienced significant cognitive impairment, seizures, or neurobehavioral symptoms. These cases illustrate a broader and more complex clinical spectrum of SPG73, extending beyond the traditionally recognized pure motor symptoms.